Vibrational spectra investigations of ytterbium chelate with isoleucine as ligand - Tuan, Le Minh; Uyen, Nguyen Trong; Bang, Nguyen Dinh (Vietnam Journal of Chemistry, 2014)
Lanthanide amino acid chelates are known to play an important role in many biological processes and prove the higher bioactivity compared to their inorganic compounds or complexes, so that there is a growing need for methods of characterizing these chelates. Raman as well as infrared (IR) spectroscopy can be used to identify as well as characterize the coordination of metal with ligand. However, the combination of both spectroscopic techniques can give a better evaluation of their molecule structures. The chelate of Ytterbium with L-isoleucine (essential amino acid) as ligand, were synthesized in ethanol-water solution and analyzed by spectroscopic means (Raman, FTIR). The comparative analysis of the IR and Raman spectra for the ligand and the complexes indicate the coordination of Ytterbium ion with the carboxylic oxygen atom and the nitrogen atom of the amino group to form chelate. Key words: Ytterbium, L-isoleucine, chelate, coordination, vibrational spectra, FT Raman, FTIR.